Mudville - Scaletta, Kurtis (Yearling, 2009)
For twenty-two years, since a fateful baseball game against their rival town, it has rained in Moundville, so when the rain finally stops, twelve-year-old Roy, his friends, and foster brother Sturgis dare to face the curse and form a team.